Pengaruh Pengetahuan Kewirausahaan, Motivasi Berwirausaha, Ekspektasi Pendapatan, dan Peran Media Sosial Terhadap Minat Berwirausaha - Siti Fatimah Nurul’aini; Ika Indriasari; Ratih Hesty Utami Puspitasari (Journal of Islamic Entrepreneurship and Business Research, 2024)
Unemployment remains a persistent challenge for many developing countries, including Indonesia, and addressing it requires innovative approaches. One potential solution is fostering entrepreneurship, which can enhance creativity and provide individuals with opportunities to develop and implement their ideas. Entrepreneurship not only supports personal economic independence but also contributes to broader economic growth. This study focuses on analyzing the factors that influence entrepreneurial interest among university students, particularly at Universitas PGRI Semarang. Specifically, it examines the impact of entrepreneurial knowledge, entrepreneurial motivation, income expectations, and the role of social media on students' entrepreneurial interest. The research employs a quantitative approach using multiple linear regression analysis and involves a sample of 100 respondents. Data were collected through structured questionnaires and analyzed using SPSS 25 for hypothesis testing. The results reveal that entrepreneurial knowledge (X1) and entrepreneurial motivation (X2) do not significantly influence students’ entrepreneurial interest (Y). However, income expectations (X3) and the role of social media demonstrate a significant positive effect on entrepreneurial interest. These findings highlight the importance of external factors, such as financial incentives and technological tools, in shaping students’ inclination toward entrepreneurship. Social media, in particular, plays a crucial role as a platform for marketing, networking, and idea generation, emphasizing its relevance in contemporary entrepreneurial ecosystems. This study underscores the need for educational institutions to integrate practical entrepreneurial strategies and digital literacy into their curricula to better prepare students for entrepreneurial ventures.